نظرية الحكومة الإسلامية عند أبي الأعلى المودودي: دراسة وصفية تحليلية في فلسفة الحكم الإسلامي - Muhamad Fajar Pramono; Amir Sahidin; Mohammad Kholid Muslih (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Religion and power are two inseparable aspects in Islam. In fact, power itself is a vital component of religious duty, as human well-being cannot be fulfilled without it. Therefore, Al-Maududi emphasized the importance of this issue, which he articulated in his theory of Islamic governance. This article will discuss the philosophy of law in Al-Maududi’s theory of Islamic governance. Based on library research, qualitative data, and a descriptive-analytical approach, the following conclusions can be drawn: first, Al-Maududi’s theory of Islamic governance is unique compared to other theories due to its balanced concept of sovereignty, neither excessive nor dismissive. Second, this theory is supported by fundamental principles of governance. Third, the theory is further supported by three essential institutions that Al-Maududi formulated: legislative, executive, and judicial. All of this demonstrates the significance of both religion and politics in Islam.